Membangun Keunggulan Ekonomi Lokal melalui Pemberdayaan Kelompok Wanita Tani di Desa Pulosari Kecamatan Jambon: Building Local Economic Excellence through Empowering Women Farmer Groups in Pulosari Village, Jambon District - Khusnul Khotimah; Mariana Mariana (Edujavare Publishing, 2023)
Sustainable economic development in rural areas is an important aspect in efforts to improve community welfare. Women farmer groups have a strategic role in advancing the agricultural sector and driving the wheels of the local economy. This service activity aims to build local economic excellence through empowering groups of women farmers in Pulosari village, sub-district. The service method uses the ABCD (Asset-Based Community Development) approach in strengthening the economy of women farming groups in Pulosari Village. Activities carried out in this service include assistance with laundry, assistance with Amrin catering, assistance with Azriel for planting seeds and crickets, assistance with the source of blessings cooperative and food processing efforts by members. The results of the service are: Identifying the potential, abilities and assets possessed by the women farmer group in Pulosari Village by focusing on the group of women farmers who are a source of many blessings who have potential, abilities and assets that can improve the local economy. Encouraging collaboration between women farmer groups and government, private and community institutions in the development of economic businesses carried out by the district and central Jakarta food security and agriculture services. Providing increased knowledge and skills of women farmer group members in managing economic businesses through sharing, mentoring and joint efforts in the blessing source women farmer group.